Karakter Morfo-Fisiologi Daun, Penciri Adaptasi Kedelai terhadap Intensitas Cahaya Rendah - , Kisman; Nurul Khumaida; , Trikoesoemaningtyas; , Sobir; Didy Sopandie (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
The main objective of this study was to identify the leaf morpho-physiological characters as markers for adaptation of soybean to low light intensity. The field experiment was conducted using split plot design with 3 replications. First factor was soybean genotype consisted of shade tolerant genotypes (Ceneng, Pangrango) and sensitive genotypes (Godek, Slamet). Second factor was low light intensity consisted of: L0 = control (under full sun light), L1 = 5 days under 50% shading (exposed after 21 days after planting/DAP), L2 = 5 days under dark condition (exposed after 21 DAP), L3 = 3 days 50% shading + 5 days sun light (exposed after 18 DAP), dan L4 = 3 days 50% shading + 3 days sun light + 5 day dark conditions (exposed after 15 DAP). The 50% shading was made artificially using black plastic paranet with 50% light transmitted. Results of this study showed that under the conditions of low light intensity, leaf morpho-physiological characters of soybean that could be used as markers for adaptation were leaf area, specific leaf weight, and chlorophyll content. Leaves of shade tolerant genotypes were wider and thinner and also contained higher chlorophyll especially for chlorophyll b than that of shade sensitive genotypes under low light intensity.   Key words :  Low light intensity, tolerant genotype, leaf area, chlorophyll, specific leaf weight